PENINGKATAN HASIL BELAJAR SISWA MATERI JURNAL PENUTUP DENGAN METODE TEAM ASSISTED INDIVIDUALIZATION DILENGKAPI PEMBERIAN TUGAS - Anis Istibsyaroh, (Pendidikan Ekonomi, 2012)
This study aimed to find out that the application of the provision of tasks completed TAI (Team Assisted Individualization) can improve student learning outcomes in the journal cover lesson material accounting services firms and how they respond to the model. The subject of this study is the eleventh-grade students in high school social studies 2 Mojokerto. Data were collected through observation, testing, questionnaires, and documentation. These data were then analyzed descriptively. Studies show that the use of TAI in the lessons improve student learning outcomes significantly.